Who is Lying and Who is Telling the Truth? : An Examination of Children’s Concept of Lying - Major, Lenke (Studies in Teaching and Education, 2024)
By developing social skills, we can enable individuals to ensure that their behavior is socially acceptable and not harmful to others. For children, what is good and bad does not necessarily align with what society deems acceptable. Our research investigates whether upper elementary and adolescent children view lying in the same way as adults or if they perceive various lying situations and elements of lying differently. In our work, we present the developmental process of children’s moral values and the factors characteristic of prototypical lies that influence their perception of lying. Our research question focuses on whether adolescent children view lying in the same way as adults or if they perceive various lying situations and elements of lying differently. In our study, we replicated Coleman and Kay’s experiment on lying using their measurement tool adapted to the Hungarian language. The study was conducted among upper elementary students who are native Hungarian speakers in Serbia. The results show that children think differently from adults regarding their perception of lying and their evaluation of the complex elements that constitute lies. Our research highlights the crucial role of institutional education in shaping moral values and developing social competence.